Pulmonary Alveolar Proteinosis: Conducting the first Whole Lung Lavage in Nepal - Uprety, A.; Bhatta, N.; Shahi, R.; Varma, A.; Dhakal, Y.; Aryal, P.; Yadav, D.K.; Chaudhary, S.; Hamal, S.; Mishra, D.R. (Nepalese Respiratory Journal, 2023)
A case of Pulmonary Alveolar Proteinosis, probably secondary in etiology, was diagnosed at our institute based on clinical, radiological, and pathological evidence. Patient was planned for conducting whole lung lavage as per the guidelines. With this case, we report the first instance of conducting Whole lung lavage in Nepal and the logistics involved.